2003
DOI: 10.1093/ndt/gfg093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vascular calcification in ESRD patients using spiral CT

Abstract: In ESRD patients, the factors correlating with coronary calcification were duration of dialysis and advancing age, whereas only age correlated with aorta calcification. Spiral CT offers an alternative technique for the assessment of these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
86
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 19 publications
9
86
0
6
Order By: Relevance
“…While the median scores in the present study were similar to CAC scores in several recent studies employing EBCT (9,22), the median was larger. The differences may reflect the higher mean age of our patient population (61 vs. 49 or 57 years), or longer duration of dialysis (80 vs. 25 or 37 months).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…While the median scores in the present study were similar to CAC scores in several recent studies employing EBCT (9,22), the median was larger. The differences may reflect the higher mean age of our patient population (61 vs. 49 or 57 years), or longer duration of dialysis (80 vs. 25 or 37 months).…”
Section: Discussionsupporting
confidence: 84%
“…Recent new software adaptations and increased speed of gantry rotation have allowed the use of spiral CT scans to quantify CAC. However, there has been only one evaluation of CAC in dialysis patients using spiral CT (9).…”
Section: Introductionmentioning
confidence: 99%
“…Several noninvasive methods are available to detect and measure the degree of aortic VC. Computed tomography (CT) constitutes the gold standard for quantification of VC and, being the most effective and widely available with reproducible measurements, is also useful for monitoring progression as well as assessing the effect of therapeutic strategies to modify progression (16,17) (Figure 1). Lateral lumbar radiographs can also accurately detect aortic calcification and may even distinguish between intimal and medial calcification (9).…”
mentioning
confidence: 99%
“…[6,7] Several reports have discussed methods for estimating vascular calcification in hemodialysis patients, including the allocation of a coronary artery calcification score using electron beam CT or spiral CT, measurement of areas of abdominal aortic calcification using abdominal CT, and creating an aortic calcification score using a cross-section of the abdominal aorta that has been divided into 12 sections on the abdominal CT image. [6][7][8][9][10][11][12][13][14][15][16][17] All of these procedures are difficult to do routinely.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that vascular calcification increases cardiovascular events and mortality. [1][2][3][4][5] Several reports have discussed the use of different imaging modalities for assessing vascular calcification, including assessment of coronary artery calcification using electron beam computed tomography (CT) or spiral CT and assessment of the calcification index of the abdominal aorta using plain abdominal CT. [6][7][8][9][10][11][12][13][14][15][16][17] However, these modalities are of limited use because of their high cost, and their use as screening tools is restricted. Simple posterior-anterior chest x-rays are carried out regularly in many hemodialysis clinics to adjust patients' post-dialysis dry weights.…”
Section: Introductionmentioning
confidence: 99%